Age-based weight estimation. Comparison of the formulas in a Peruvian sample - Sihuay-Torres, Kamila (2018)
Objective: To describe a weight estimation formula from the age of children attended in a Pediatric Dentistry Clinic and compare its accuracy with standard formulas. Methods: A cross-sectional, observational study that included 165 children between three and ten years of age who presented to the pediatric dentistry consultation. Linear regression analysis allowed prediction of weight according to the variation of the age of the sample studied. The derived formula was analyzed according to its accuracy and accuracy through mean percentage errors, 95% limits and through Bland-Altman diagrams compared to the Luscombe, APLS, Tinning and Argall formulas. Results: The average weight was 26.81±8.46 kg. The prediction formula was: Weight in kilograms = 3 (age in years) + 7. The Luscombe formula obtained an average error rate of -2.69%, the APLS formula of 17.87%, while Argall formula 1.41. The 53.9% of the estimates were within the 10% weight measured for the Luscombe formula and 47.3% for the Argall formula. Conclusions: The estimated formula resembled that of Luscombe being the most accurate in the sample studied and the one that has a greater approximation to the real weight.